The Meaning of Religiosity of The Munjong Traditional Ceremony - Seko, Salfius; Soa, Alfonsus Hendri; Lolita, Lolita (Universitas Tanjungpura, 2024)
The expression of gratitude of the Dayak Tobag community to Jebata is expressed in the form of gratitude called Munjong. Munjong has a meaning as an expression of gratitude for all gifts, fortune / harvest, protection and welfare as well as a form of restoration of relationships that have been damaged due to human behaviour in relation to the cosmos. The purpose of this research is to understand the religio magical meaning of the munjong traditional ceremony from the perspective of Dayak Tobag. This research uses empirical/sociological legal research methods using a phenomenological approach and hermeneutic theory so that it is known that the Dayak Tobag people see everything as a gift, a gift and everything that exists is centred and there is someone who makes it, namely SANG-ADA who makes everything exist and is the centre of everything that exists. All events and activities in relation to nature (cosmos) and humans in the Tobag Dayak community are seen in a transcendental dimension culminating in an expression of gratitude. The expression of gratitude in the Tobag Dayak perspective is manifested in a traditional Munjong ceremony.